Basaloid squamous cell carcinoma of the tonsil: report of a case and review of the literature - Shetty, Deviprasad; Subramaniam, Vijayalakshmi; Herale, Adarsha; Saldanha, Prema; Jain, Mahaveer (Contemporary Oncology/Współczesna Onkologia, 2012)
The most common type of malignancy affecting the upper aerodigestive tract is squamous cell carcinoma. Basaloid squamous cell carcinoma (BSCC) is a rarely seen, high-grade, bimorphic variant of squamous cell carcinoma, which displays distinct histological features. This entity was first described by Wain et al. in 1986. Since then, approximately 170 cases of head and neck basaloid squamous cell carcinoma have been reported. Tonsils are an uncommon site of occurrence of basaloid cell carcinoma. Only 10 cases of basaloid squamous cell carcinoma arising in the tonsils have been described in current English literature. Histopathologically, these carcinomas are characterised by the presence of a basaloid component in close association with squamous cell carcinoma. In this article, a case of BSCC of the tonsil is reported. The clinical and histopathological features of this tumour are discussed. Relevant literature has been reviewed and differential diagnosis of this tumour is discussed.